Optic Nerve Avulsion Following Accidental Penetrating Orbital Injury - Akhanda, AdministratorAH; Ahamed, T; Ahmad, AU (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jul;17(2):197-200. The abstract of this article is available on the PubMed website